2017
DOI: 10.1002/jccs.201700130
|View full text |Cite
|
Sign up to set email alerts
|

A Green Route to Produce Adipic Acid on TiO2–Fe2O3 Nanocomposites

Abstract: In this work, we study cyclohexene oxidation by molecular oxygen on doped-TiO 2 . The improvement of the oxidizing capacity of titanium oxide by doping with iron oxide at different molar ratios is checked. All materials with different molar ratios (Ti/Fe = 9, 4, and 2) are prepared by the sol-gel method and fully characterized by ICP, XRD, SEM, DR/UV-vis, IR, and N 2 adsorption/desorption. The results show that iron is successfully incorporated into the titanium matrix but the incorporated amount is limited. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Cyclohexene oxidation is one of the most used reactions in the manufacture of fine chemical products [1,2], largely used in different applications and fields [3,4]. Scheme 1 demonstrates the different products that can be obtained from cyclohexene oxidation [1][2][3][4]. The literature evoked the formation of more than seventy products and intermediates (gas, liquid and solid phases) from this reaction depending on the reaction conditions i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclohexene oxidation is one of the most used reactions in the manufacture of fine chemical products [1,2], largely used in different applications and fields [3,4]. Scheme 1 demonstrates the different products that can be obtained from cyclohexene oxidation [1][2][3][4]. The literature evoked the formation of more than seventy products and intermediates (gas, liquid and solid phases) from this reaction depending on the reaction conditions i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Adipic acid is one of the most important commercially available aliphatic diacarboxylic acids with a large industrial application in Nylon-6 and Nylon-66 manufacture, and intermediates for pharmaceuticals and insecticides [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic liquid‐phase epoxidation of cyclohexene is a commercially important reaction that is used to produce cyclohexene oxide, which is an essential organic intermediate in the production of fine chemicals. Moreover, the production of epoxides paves the way to the development of mild and green chemical processes for the synthesis of adipic acid, which is the raw material used in the production of nylon 6,6 . The use of solid catalysts for cyclohexene epoxidation, using TBHP as oxidant, has been reported, with the formation of 2‐cyclohexene‐1‐one, 2‐cyclohexene‐1‐ol, and trans ‐cyclohexane‐1,2‐diol, besides cyclohexene oxide …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that cyclohexene epoxidation is affected by multiple parameters, such as the type of oxidant, molar ratio of cyclohexene to the oxidant with various cyclohexene/oxidant molar ratios, temperature, heating mode, catalyst weight, support, and the percentage of active phase to be deposited on the support ( x %/support) . Each group of researchers proposed some specific operating conditions for the reaction.…”
Section: Introductionmentioning
confidence: 99%